Предмет: Математика, автор: CofiaFilippova

помогите пожалуйста ​

Приложения:

Ответы

Автор ответа: ludmilaksenija2005
1

Пошаговое объяснение:

1) -5 6/7•3/13= -41/7•3/13= -123/91

2) -123/91•(-4 1/3)= -123/91•(-13/3)=

=41/7=5 6/7


CofiaFilippova: спасибо
Автор ответа: oleksandrtkach2000
1

Ответ: 5 6/7

Пошаговое объяснение:

(-5 6/7*3/13)*(-4 1/3)=(-41/7*3/13)*(-13/3)=(-41/7*3/13)=-\frac{41*3}{7*13}=-123/91=(-123/91)*(-13/3)=123/91*13/3=41/7*1/1=\frac{41*1}{7*1}=41/7=5 6/7


CofiaFilippova: спасибо
Похожие вопросы